The Position and Influence of Persian and Persian Poets on Theorists of Islamic Literature - Moslem Gorji; Sardar Aslani; Mohammad Rahimi Khooyegani (ادبیات تطبیقی, 2022)
IntroductionThe emergence of Islamic literature can be considered as coinciding with the emergence of Islam; however, the literary theories that have been used based on Islam and as theories of Islamic literature have occurred in the contemporary period. For the first time in India, Abolhassan Nadvi introduced the theory of Islamic literature and held various congresses to invite people to Islamic literature. He also formed the Association for the Relationship of World Islamic Literature. Under his supervision, many activities were carried out in the field of inviting to Islamic literature and supporting the theorists, writers and activists of Islamic literature in this association. Following Abolhassan Nadvi’s  invitation, many writers responded to his request. Some of them theorized in the field of Islamic literature. Among them, five are considered as the main theorists of Islamic literature, which consist of Abul Hassan Nadvi in India; Sayyid Qutb, Muhammad Qutb, and Najib Kilani in Egypt; and Emad al-Din Khalil in Iraq.   MethodologyThis research has been done using descriptive-analytical and content analysis methods. In it, the statements and statements of the theorists of Islamic literature about Persian language poets and Persian language are discussed. In the meantime, he has relied on the books of Abu al-Hassan Nadvi, Muhammad Qutb, Sayyid Qutb, Najib Kilani, and Emad al-Din Khalil, as the main theorists of Islamic literature. DiscussionWhat is important to consider is that the theorists whose names have been mentioned, in their theorizing, and to prove Islamic literature, have cited the poetry of Persian and non-Iranian Persian poets. Among the poets who have had the most influence on the theorists of Islamic literature are: Mohammad Iqbal Lahori, Maulana Jalaluddin Mohammad (Rumi), Hafez, Saadi, and some other Iranian poets, and some other poets whose names have merely been mentioned in the researches of these theorists consist of Sanai, Attar Neyshabouri, Khayyam, customary, Iraqi, Ghodsi, etc. It goes without saying that if Najib Kilani, Mohammad Qutb, Sayyid Qutb, and Emad al-Din Khalil speak of Iqbal, his poetry, and his Islamic thought, or if they refer to the poetry of Saadi, Hafez, and other Persian-speaking poets as Islamic literature, all are due to the efforts of the first theorist of Islamic literature in India called Abolhassan Nadvi. Following him, other theorists also benefited from his achievements. In addition, they paid special attention to the literature of Persian speakers and especially Iranian poets. Accordingly, Persian language literature, especially Iranian literature, has had a significant impact on the emergence of theories of Islamic literature.The position and influence of Persian and Persian poets on theorists of Islamic literatureNadvi's acquaintance with Persian literature got him to pay special attention to Iranian literature. Had it not been for his efforts to introduce the Persian language and Islamic literature to Persian poets, other theorists of Islamic literature would have neglected the most important source of Islamic literature. As a result, this is why we see that the amount and volume of dealing with Persian language and literature of Persian language poets in Nadvi is more than other theorists of Islamic literature. Among the theorists, following Nadvi, poets like Najib Kilani and Mohammad Qutb inclined toward Iqbal Lahori’s literature. Emad al-Din Khalil's tendency is towards the poetry of Rumi and Saadi. In the meantime, Hafez has had a great impact on Sayyid Qutb.The influence of Persian poets on theorists of Islamic literatureAfter examining the position of Persian language and literature on theorists of Islamic literature, we examine the influence of the most important Persian language poets on theorists of Islamic literature. Meanwhile, we examine four prominent poets consisting of Mohammad Iqbal Lahori, Maulana Jalaluddin Mohammad, Hafez and Saadi Shirazi.Mohammad Iqbal LahoriIqbal Lahori can be considered the first and most important Persian poet who has had the great impact on the formation of Islamic literature. His acquaintance with Abul Hassan Al-Nadvi and their meetings may be the basis of Nadvi's motivation to invite him to Islamic literature. In addition to the meeting between Nadvi and Mohammad Iqbal, Abolhassan Nadvi's acquaintance with the Persian caused him to become acquainted with the poems and thoughts of Mohammad Iqbal. The more he became acquainted with Iqbal's literature and thoughts, the more he became influenced by Iqbal. In addition to Iqbal's poetry and his Islamic characteristics, another important point about Iqbal that Nadvi pays attention to is the very character of a Muslim writer. He sees this character in Iqbal.Another theorist of Islamic literature, Mohammad Qutb, views Iqbal's poetry as an excellent model of Islamic literature. In his famous book "Islamic Methodology", he introduces his poetry as a successful example in Islamic literature. In reviewing Iqbal's poetry, Mohammad Qutb shows the human and Islamic dimension of his poetry. In addition, the human dimension of his poetry considers him universal, which is rooted in Islamic thought and ideas.Egyptian theorist of Islamic literature Najib Kilani was also influenced by Iqbal's poems. Although he was not familiar with Persian language, Dr. Abdul Wahab Azzam's translations of Iqbal's poems were enough to draw Kilani to Islamic literature. Kilani wrote the book Iqbal al-Sha'ir al-Tha'ir while in prison (for his political activities). Like Nadvi, Kilani admired Iqbal and was influenced by him. Kilani  also appreciates Iqbal on a number of occasions and he acknowledges his influence on his poetry.Emad al-Din Khalil, a theorist of Iraqi Islamic literature, is also influenced by Iqbal in his poems. To the extent that Hafez Abdul Qadir reveals this influence in his review of Emad al-Din Khalil's DivanJalaluddin Muhammad BalkhiAbul Hassan Nadvi mentions Rumi as another example of Muslim writers who has taken steps to enhance Islamic literature, and in his literature he traces the subtle human characteristics such as love, beauty and human worth. Nadvi in the book "Comments on Literature" in a chapter entitled "Literature of love, affection, respect for man and humanity in the poetry of Maulana Jalaluddin Rumi" introduces Maulana and his literature. Rumi's Islamic poetry is mentioned as a beginning to compose human value and dignity. He believes that in a world that does not believe in the value and position of mankind, Rumi echoes the correct Islamic idea in his poetry. He builds a new foundation for Islamic literature on the ruins of pessimistic literature and unpopular poetry of the time. It begins with composing human dignity and introduces human dignity and honor.Emad al-Din Khalil, in his book entitled "New Developments in Islamic Criticism", examines a selection of Rumi's Masnavi. He considers Rumi as an important poet in Islamic literature. In his study, from the very beginning, Rumi's amazing power in illustration and imagination amazes him. In addition, his poetic power and his ability to maintain his commitment to Islam in his poems make him admire Rumi. He believes that he has been able to portray Islamic ideas in the best way throughout his poems.Hafiz ShiraziAmong the theorists of Islamic literature, Seyyed Qutb was more fascinated by Hafez than other theorists. He found himself lost in Hafez's poems. He was looking for something that would enrich Arabic poetry, free it from the influences of Western philosophies, and get acquainted with Islamic thoughts and Islamic literature. He had found all these elements together in Hafez's poetry. He considers Hafez's lyric poems as the savior of Arabic literature from the contemporary crisis, and in addition to saving and inspiring Arabic poetry, Hafez's poetry, according to Sayyid Qutb, instills the spirit of the East in the composition of the Arab world, and frees it from boring Western rationalism.Sa'di ShiraziNadvi speaks of the Indians' attention to reading Saadi's books Golestan and Bustan. He points to the effects of these two books on moral and social education in human beings, in addition to believing that these two books provide life experiences to the audience. Besides Nadvi's acknowledgment of the moral and educational impact of Saadi's works in India, he cites Saadi's poems as a clear example of Islamic literature. ConclusionBased on what has been said, it can be concluded that Persian language was considered by theorists of Islamic literature because of its characteristics. It is considered as a central language in all theories of Islamic literature. The global position of Persian literature attracted more attention to it. Moreover, what led the theorists of Islamic literature to pay attention to Iranian literature was the Islamic dimension of the literature of this Islamic land.Additionally, Mohammad Iqbal had the greatest influence on theorists of Islamic literature. However, Iqbal Vandavi himself believes that Iqbal was also influenced by the Iranian poet Maulana Jalaluddin. In the meantime, after Iqbal and Rumi Jalaluddin, Saadi's influence is more due to his two valuable books (Bustan and Golestan). Overall, most of Saadi's influence can be seen in Nadvi. In contrast, Hafez has had the greatest impact on the Egyptian theorist Sayyid Qutb, who was fascinated by him.